EVALUATION OF INFRASTRUCTURE NETWORK NOSES PADANG CITY GEOSPATIAL INFORMATION - ikhlas, fahmi yasir; Yulfa, Arie (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
Spatial data infrastructure (IDS) is the implementation of data infrastructure within the framework of geographic data, metadata, users, and interactively connected tools to effectively utilize spatial data. Spatial data infrastructure (IDS) plays an important role in the management of geospatial information in decision making, planning, development and utilization of natural resources and regional development. In the IDS development process, the role of network nodes contributes to the deployment of spatial data. In this study, data was collected from Diskominfo Kota Padang. The purpose of this study is to determine the readiness of IDS Kota Padang in providing geospatial information and then conduct an assessment. The type of research used is quantitative research with survey methods with Diskominfo through the distribution of questionnaires. Data analysis techniques in this study are literature study research and social network analysis. The results showed that the level of readiness of IDS Diskominfo in all aspects was calculated at 56% which was the result of the sum of all variables and was included in the Quite Ready category.